Sexually dimorphic and asymmetric effects of embryonic ethanol exposure on hypocretin/orexin neurons as related to behavioral changes in zebrafish - Adam D. Collier (Nature Portfolio, 2021)
Abstract Neurons expressing the neuropeptide hypocretin/orexin (Hcrt) in the hypothalamus promote reward-related behaviors including alcohol consumption and are shown in rodents and zebrafish to be stimulated by embryonic exposure to ethanol (EtOH). We used here in zebrafish three-dimensional analyses of the entire population of Hcrt neurons to examine how embryonic EtOH exposure at low-moderate concentrations (0.1% or 0.5% v/v) alters these neurons in relation to behavior. We found that EtOH in the water for 2 h (22–24 h post fertilization) increases the number of Hcrt neurons on the left but not right side of the brain through a stimulation of cell proliferation, this is accompanied by a decrease in locomotor activity under novel conditions but not after habituation, and these effects are evident in both larvae and adults indicating they are long lasting. Our analyses in adults revealed sexually dimorphic effects, with females consuming more EtOH-gelatin and exhibiting more freezing behavior along with an asymmetric increase in Hcrt neurons and males exhibiting increased aggression with no change in Hcrt. These findings suggest that a long lasting, asymmetric increase in Hcrt neurons induced by EtOH results from an asymmetric increase in proliferation specific to Hcrt and contributes to behavioral changes in females.